Protein Disulfide-Isomerase A3 Is a Robust Prognostic Biomarker for Cancers and Predicts the Immunotherapy Response Effectively - Tu, Zewei; Ouyang, Qin; Long, Xiaoyan; Wu, Lei; Li, Jingying; Zhu, Xingen; Huang, Kai (Frontiers in Immunology, 2022)
Background: Protein disulfide isomerase A3 (PDIA3) is a member of the protein disulfide isomerase (PDI) family that participates in protein folding through its protein disulfide isomerase function. It has been reported to regulate the progression of several cancers, but its function in cancer immunotherapy is unknown. Methods: The RNA-seq data of cancer and normal tissues were downloaded from The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression (GTEx) databases. Cbioportal dataset was used to explore the genomic alteration information of PDIA3 in pan-cancer. Human Protein Atlas (HPA) and ComPPI websites were employed to mine the protein information of PDIA3, and western blot assay was performed to monitor the upregulated PDIA3 expression in clinical GBM samples. The univariate Cox regression and Kaplan-Meier method were utilized to appraise the prognostic role of PDIA3 in pan-cancer. Gene Set Enrichment Analysis (GSEA) was applied to search the associated cancer hallmarks with PDIA3 expression. TIMER2.0 was the main platform to investigate the immune cell infiltrations related to PDIA3 in pan-cancer. The associations between PDIA3 and immunotherapy biomarkers were performed by spearman correlation analysis. Findings: PDIA3 is overexpressed in most cancer types and exhibits prognosis predictive ability in various cancers. In addition, PDIA3 is significantly correlated with immune-activated hallmarks, cancer immune cell infiltrations and immunoregulators, and the most interesting finding is that PDIA3 could significantly predict anti-PDL1 therapy response. Finally, specific inhibitors which correlated with PDIA3 expression in different cancer types were also screened by using Connectivity Map (CMap). Interpretation: The results revealed that PDIA3 acts as a robust tumor biomarker. Its function in protein disulfide linkage regulation could influence the protein synthesis, degradation and secretion, and then shapes the tumor microenvironment, which might be further applied to develop novel anti-cancer inhibitors.